2016
DOI: 10.18632/oncotarget.8894
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 increases SLC7A7 expression and proliferation of pig intestinal epithelial cells

Abstract: Nutrient absorption mediated by nutrient transporters expressed in the intestinal epithelium supplies substrates to support intestinal processes, including epithelial cell proliferation. We evaluated the role of Caudal type homeobox 2 (CDX2), an intestinespecific transcription factor, in the proliferation of pig intestinal epithelial cells (IPEC-1) and searched for novel intestinal nutrient transporter genes activated by CDX2. Our cloned pig CDX2 cDNA contains a "homeobox" DNA binding motif, suggesting it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…For CDX2, an intestine-specific TF with a role in the proliferation of porcine intestinal epithelial cell line one, novel intestinal nutrient transporter genes activated by CDX2 were screened (15). The transcription initiation site of miR-145-5p has been predicted use jaspar software (http://jaspar.genereg.net/).…”
Section: Resultsmentioning
confidence: 99%
“…For CDX2, an intestine-specific TF with a role in the proliferation of porcine intestinal epithelial cell line one, novel intestinal nutrient transporter genes activated by CDX2 were screened (15). The transcription initiation site of miR-145-5p has been predicted use jaspar software (http://jaspar.genereg.net/).…”
Section: Resultsmentioning
confidence: 99%
“…The control, LGR5 -overexpressing and BMI1 -overexpressing cells were cultured in six-well plates (Corning Inc., Corning, NY, USA) at a density of 1 × 10 5 cells/mL in growth medium for 48 h and collected for real-time PCR analysis as previously described [ 40 ]. The gene-specific primers were designed with Primer 5.0 software (Premier Biosoft International) and are detailed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, the functional effects of CDX2 on the proliferation of normal intestinal epithelial cells are diverse. Studies on normal intestinal epithelial cells such as IEC-6 [ 7 ], IPEC-1 [ 8 ], blastocysts [ 9 ], and ISCs [ 10 ] revealed that CDX2 stimulates cell proliferation. In addition, porcine milk-derived exosomes increase CDX2 protein expression and IPEC-J2 cell proliferation simultaneously, suggesting that cell proliferation and CDX2 expression do not conflict [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cancer cells, including human colorectal carcinoma cells (HT-29) [ 5 ], human colon adenocarcinoma cells (Caco-2) [ 4 ] and gastric cancer cells (BGC-823) [ 6 ], demonstrated that CDX2 inhibits cell proliferation. However, studies on rat intestinal epithelial cells (IEC-6) [ 7 ], porcine intestinal epithelial cells (IPEC-1) [ 8 ], blastocysts [ 9 ], and mice ISCs [ 10 ] produced opposite results, accompanied by high expression of Heparin-binding epidermal growth factor (EGF) like growth factor and proliferating cell nuclear antigen (PCNA) [ 7 ]. Therefore, it is still unknown how CDX2 plays dual roles in different types of cells.…”
Section: Introductionmentioning
confidence: 99%